PENINGKATAN KEAKTIFAN SISWA PADA PEMBELAJARAN MATEMATIKA DENGAN METODE DEMONSTRASI DI KELAS IV MIS UJUNG BATU - Lailan Aprina Siregar; Rizki Hamdan Saputra; Misra Cahaya Hasibuan (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
This research aims to determine the activeness of student learning in class IV MIS Ujung Batu through the demonstration learning method of triangle material on flat shapes. The type of research used is classroom action research (PTK) which consists of 2 cycles,each cycle consisting of planning,implementation,observation,and reflection. This research was carried out in class IV MIS Ujung Batu. The data sources in this research are devided into two, namely (1) Primary data namely the activity of class IV students at MIS Ujung Batu totaling 30 students. (2) Secondary data is class teachers and class IV MIS Ujung Batu school. Data collection techniques in this research were obtained through observation,interviews and documentation. The data analysis technique for this research is analysis of student learning activity